Investment Decisions on the Crowdfunding Platform Based on the Theory of Planned Behavior - Yulandreano, Evan; Rita, Maria Rio (Jurnal Manajemen Bisnis, 2023)
Research aims: Few studies on crowdsourcing have been conducted concerning Indonesian investors and fund providers. This study, therefore, aims to examine the role of investment intentions by investors with the influence of attitudes, subjective norms, and perceived behavioral control for investment decisions and the role of investment intentions as mediating variables on the relationship between perceived behavioral control and investment decisions.Design/Methodology/Approach: The research sample involved 100 investor respondents on a crowdfunding platform that had obtained permission from the Financial Services Authority (OJK). The analysis in this study then utilized PLS-SEM with SmartPLS 3.0.Research findings: The study results demonstrated that while attitudes and perceived behavioral control positively affected investment intentions, subjective norms did not. Besides, perceived behavioral control positively affected investment intentions and crowdfunding investment decisions. Meanwhile, investment intention had a positive effect on crowdfunding investment decisions.Theoretical Contribution/Originality: This study used the Theory of Planned Behavior (TPB) to examine the role of investment intention by investors with the influence of attitudes, subjective norms, and perceived behavioral control for investment decisions and the role of intention as a mediating variable on the relationship between perceived behavioral control and investment decisions.Practitioners/Policy Implications: The implications of research in crowdfunding decision-making based on investors’ considerations are attitudes, perceived behavioral control, and investment intentions.Research Limitations/Implications: This research was limited to investment decisions in TPB-based crowdfunding only, so further research is needed to observe other aspects besides psychological factors, such as testing the level of education, income, gender, and others, that may strengthen investment decisions on the crowdfunding platform.